2001
DOI: 10.1034/j.1600-0501.2001.012004358.x
|View full text |Cite
|
Sign up to set email alerts
|

Bicortical titanium screws for critical orthodontic anchorage in the mandible: a preliminary report on clinical applications

Abstract: Critical anchorage during orthodontic treatment in the mandible needs both time and effort and patient compliance. In 8 patients, 12 bicortical titanium screws (BIS) were used as anchorage units for orthodontic molar protraction. The criteria for patient selection were: critical anchorage in the lower jaw (i.e. retraction of anterior teeth undesirable) and molar extraction sites. After insertion of the screws in local anesthesia, orthodontic forces were applied immediately. One screw worked loose and had to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
96
0
38

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(136 citation statements)
references
References 6 publications
2
96
0
38
Order By: Relevance
“…[1][2][3][4][5][6][7] However, failure rates of approximately 10%-30% as described in the literature are still not satisfactory. [8][9][10][11] A sufficient primary stability measured by insertion torque seems to play a major role for the treatment time survival rate.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] However, failure rates of approximately 10%-30% as described in the literature are still not satisfactory. [8][9][10][11] A sufficient primary stability measured by insertion torque seems to play a major role for the treatment time survival rate.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] According to experimental and clinical studies, OMIs can provide sufficient and stable anchorage for orthodontic treatment. 2,[6][7][8][9][10] However, the success rates of OMIs have been reported to range from 37% to 97%. [11][12][13][14][15][16][17][18][19][20][21][22] Studies have found that the stability of OMIs is affected by age, sex, craniofacial skeletal pattern, site and side of implantation, latent period, loading protocol, dimension of OMI, angulation of OMI to bone, insertion torque, degree of OMI-bone contact, quality and quantity of the cortical bone, degree of inflammation of the peri-OMI tissue, thickness and mobility of the soft tissue, and root proximity.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is achieved by mechanical contact between the miniscrew surface and bone 3 and depends on the characteristics of devices 4,5 , insertion technique 4 and bone quality and quantity of the receptor site. 4,[6][7][8] The primary stability plays an important role in the successful secondary stability of miniscrews, since lack of immediate stability can lead to progressive mobility of the device and its subsequent loss. 9 In clinical use, the initial stability of miniscrews is also considered essential, because of immediate or early load applied on them in many patients.…”
Section: Introductionmentioning
confidence: 99%